Introducing Educational Technologies to Teachers: Experience Report - Thota, Neena; Negreiros, Joao (Journal of University Teaching and Learning Practice, 2015)
The dramatic rise in use of digital media has changed the way learning is taking place and has led to new ways to teach with digital technologies. In this article, we describe the experiences of teaching a course that introduces educational technologies to teachers in Macau. The course design is based on connectivism, a learning theory for the digital age that emphasizes interaction with digital media and active engagement in sharing digital artefacts. The learning outcomes are constructively aligned with learning and teaching activities and assessments. We share the insights we gained of the learning needs and the disparity in the technological skills and competencies of the students. The course design is evaluated in terms of the students' learning outcomes and progress through the stages of learning with technology. We present evidence from journal writings that show metacognition, active reflection and critical evaluation, and we identify anxiety and increased confidence with digital tools, as well as concerns about group work. This article contributes to the discussion on teachers learning to teach with technologies.